Ottawa materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950 (1939)
Miscellaneous data concerning Odawa dances and an informant. Letter of Ene (?), Denver Art Museum, Department of Indian Art, to Speck, December 7, 1939, concerning Delaware specimens. On reverse are Speck's notes on Delaware locations, according to eighteenth-century maps.